2018
DOI: 10.1093/biolre/ioy156
|View full text |Cite
|
Sign up to set email alerts
|

WBP2 shares a common location in mouse spermatozoa with WBP2NL/PAWP and like its descendent is a candidate mouse oocyte activating factor

Abstract: The sperm-borne oocyte-activating factor (SOAF) resides in the sperm perinuclear theca (PT). A consensus has been reached that SOAF most likely resides in the postacrosomal sheath (PAS), which is the first region of the PT to solubilize upon sperm-oocyte fusion. There are two SOAF candidates under consideration: PLCZ1 and WBP2NL. A mouse gene germline ablation of the latter showed that mice remain fertile with no observable phenotype despite the fact that a competitive inhibitor of WBP2NL, derived from its PPX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 46 publications
(78 reference statements)
2
24
0
Order By: Relevance
“…The molecular mass of WBP2NL is species-specific, as shown in previous studies with mouse (38 kDa), porcine (38 kDa), and bovine (32 kDa) spermatozoa [26]. WBP2 labeling was associated with an immunoreactive band at approximately 40 kDa, identical to that demonstrated in mouse spermatozoa [33]. The amount of sonication required to isolate the perforatorium has been shown to decrease the content of WBP2 in the PT, thereby accounting for a weaker than expected reactivity [33].…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…The molecular mass of WBP2NL is species-specific, as shown in previous studies with mouse (38 kDa), porcine (38 kDa), and bovine (32 kDa) spermatozoa [26]. WBP2 labeling was associated with an immunoreactive band at approximately 40 kDa, identical to that demonstrated in mouse spermatozoa [33]. The amount of sonication required to isolate the perforatorium has been shown to decrease the content of WBP2 in the PT, thereby accounting for a weaker than expected reactivity [33].…”
Section: Resultssupporting
confidence: 72%
“…To confirm the perforatorial presence of these proteins, isolated perforatorial tips were loaded and probed with each antibody for immunoblotting analysis (Figure 5B). Note that the postacrosomal identities of these proteins have previously been shown in either bovine or murid sperm studies [25, 26, 33, 36].…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Following biochemical characterization of WBP2 resulting in the knowledge of its binding partners and involvement in steroid signaling [4,5], WBP2 has since been discovered to play roles in a variety of human diseases such as hearing loss and infertility [6,7]. However, it is in the area of cancer where the investigations have been most intense.…”
Section: Wbp2 Functionmentioning
confidence: 99%
“…Mating studies with Wbp2nl KO males showed no defects in fertility, with normal size litters being produced by these males. These findings along with the previously discussed data in human sperm suggest that PAWP plays no role in egg activation in mammals, although it remains remotely possible that loss of PAWP expression is being compensated functionally by upregulation of another gene product, or by the recently reported ortholog Wbp2 (Hamilton et al, ). Hachem et al () also examined the issue of whether PAWP expression was altered following Plcz1 gene KO.…”
Section: Introductionmentioning
confidence: 99%